The Concept of 'Kafir' in the Qur'an Revisited: Comparative Insights from Marah Labid and the Ministry of Religious Affairs' Exegesis - Hidayatullah, Syarif; Abidin, Zaenal; Masuwd, Mowafg (Al-Karim: International Journal of Quranic and Islamic Studies, 2024)
Abstract: This study revisits the concept of 'kafir' in the Qur'an by conducting a comparative analysis of two prominent exegeses: Marah Labid and the Ministry of Religious Affairs' Tafsir. The objective is to explore how different interpretative frameworks affect the understanding of 'kafir' and its implications for contemporary Islamic thought. The research addresses a significant gap in the literature, as most existing studies focus on either classical or modern interpretations without comparing traditional and state-sanctioned exegeses. The study employs a qualitative content analysis method, systematically comparing the thematic and contextual interpretations in both tafsirs. The findings reveal substantial differences in the conceptualization of 'kafir,' with Marah Labid providing a more traditional and juridical perspective, while the Ministry of Religious Affairs' Tafsir emphasizes a contextual and inclusive approach. These results suggest that contemporary exegesis can influence socio-political attitudes towards non-Muslims, highlighting the dynamic nature of Qur'anic interpretation. Theoretically, the study contributes to the discourse on tafsir by demonstrating the fluidity and adaptability of Islamic exegesis in response to evolving socio-political contexts. The findings encourage further exploration of how institutional and historical contexts shape religious interpretations, ultimately affecting both theological understanding and practical engagement with religious diversity. Contribution: This study contributes to the field of Qur'anic exegesis by revealing how different interpretative frameworks in traditional and state-sanctioned tafsir influence the understanding of 'kafir' and its implications for contemporary Islamic discourse.